Cell Reprogramming: A New Chemical Approach to Stem Cell Biology and Tissue Regeneration - Anastasia, L.; Piccoli, M.; Garatti, A.; Conforti, E.; Scaringi, R.; Bergante, S.; Castelvecchio, S.; Venerando, B.; Menicanti, L.; Tettamanti, G. (Current Pharmaceutical Biotechnology, 2011)
Generation of pluripotent stem cells (iPSCs) from adult fibroblasts starts a “new era” in stem cell biology, as it overcomes several key issues associated with previous approaches, including the ethical concerns associated with human embryonic stem cells. However, as the genetic approach for cell reprogramming has already shown potential safety issues, a chemical approach may be a safer and easier alternative. Moreover, a chemical approach could be advantageous not only for the de-differentiation phase, but also for inducing reprogrammed cells into the desired cell type with higher efficiency than current methodologies. Finally, a chemical approach may be envisioned to activate resident adult stem cells to proliferate and regenerate damaged tissues in situ, without the need for exogenous cell injections.
Keywords: retroviruses